The Development of a Skincare Routine Expert System - Abdullah, Nurzahidah; Hasan Basari, Abd Samad (Applied Information Technology And Computer Science, 2022)
Nobody wishes to have great skin. However, various factors, especially environmental exposures to bad behaviors, can unintentionally destroy facial skin. As a result, it is critical that you take care of your facial skin on a regular basis. Everyone has a unique skin type on their face. Normal, sensitive, dry, oily, and combination skin types exist. A facial skin care routine is essential for everyone, regardless of skin type. Our face will shine brighter, smoother, and more radiant, with regards to providing healthier facial skin. As a result, this expert system is designed to provide users with recommendations and consultations about the type of skin they have, and also advice or solution aimed at preventing the formation of more serious issues. There are two categories of users involved: administrators and users at the user level. The system is developed with the Hypertext Processor (PHP) as the programming language and MYSQL as the database system